Strategies For Strengthening Employee Performance: The Synergistic Influence Of Training, Compensation, And Motivation At PT PCI Elektronik Internasional: - Atmojo , Agus Sekti Susila; Nuraeni , Brigida Endah; Sumarya , Edi (Tractare: Jurnal Ekonomi-Manajemen, 2025)
This study aims to analyze the effect of training, compensation, and motivation on employee performance in the Quality Department of PT PCI Elektronik Internasional in Batam City. The research approach used is quantitative, with 89 respondents determined using the Slovin formula. Data collection was carried out through an online questionnaire using Google Forms, and the data was analyzed using SPSS software. The results showed that training had a positive and significant effect on employee performance (account = 4.921> stable = 1.662; significance 0.000 <0.05). Motivation also showed a positive and significant effect (account = 4.514> ttable = 1.662; significance 0.000 <0.05). However, compensation showed a significant negative effect on performance (account = -2.316 <ttable = 1.662; significance 0.023 <0.05). Simultaneously, the three variables have a significant effect on performance (Fcount = 74.156 > Ftable = 2.71; significance 0.000 < 0.05). The contribution of training, compensation, and motivation variables to employee performance is 72.4%, while 27.6% is influenced by other factors outside this study. These results indicate that training and motivation are the main strategies for improving performance, while the compensation system needs to be reviewed. Keywords: Training, Compensation, Motivation, Employee Performance, Quality Department